Government incentives as a factor in the development of the global electric vehicle market (the case of european experience) - Shuba, O.; Shuba, M.; Chala, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The European experience in promoting the development of electric vehicles, particularly in countries such as Germany, France, the Netherlands, Belgium, and Norway, confirms the effectiveness of a comprehensive approach that combines tax incentives, direct subsidies, and the active development of charging infrastructure. The highest results in this field have been achieved in Norway, where the share of battery electric vehicles (BEVs) among new registrations has reached almost 90%. This was made possible thanks to long-term tax exemptions as well as a high level of environmental awareness among the population. In the Netherlands and Belgium, stable growth is ensured by regional subsidy programs and the high density of the charging network. In contrast, in Germany and France, the pace of electric fleet expansion has slowed due to a reduction in the volume of government financial support. Despite differences in instruments and institutional approaches, a common trend is the clear dependence of the level of electromobility on the stability of state policy in this area and the scale of investment in related industries. The analysis of international experience, along with current trends in the development of the Ukrainian market, makes it possible to identify a number of state policy tools adapted to the current socio-economic conditions. In the context of political and economic instability, the short-term perspective of state intervention should focus on measures with high efficiency and moderate budgetary costs. Such measures include: the development of charging and service infrastructure for electric transport; the introduction of preferential loan and leasing programs for the purchase of electric vehicles; and stimulating consumer demand through targeted support programs for specific social or professional groups. Furthermore, in the post-war economic recovery phase, it is advisable to outline priority areas for the development of the electric vehicle market that could become drivers of transport system modernization, reduction of energy dependence, and enhancement of environmental security. These include: increasing transparency in state regulation mechanisms, which will strengthen investor and consumer confidence, ensure fairness and openness of market processes, and reduce the risks of corruption and abuse by officials; integrating electric vehicle market development policy with other strategic areas of state policy, particularly energy, transport, and climate, which will enable the formation of a comprehensive and balanced approach to post-war infrastructure and economic modernization as a whole; strengthening state financial support for the development of the alternative energy resources sector, which is critically important for reducing the national economy’s dependence on fossil fuel imports and ensuring the country’s long-term energy security.